2020
DOI: 10.1097/paf.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Magnetic Resonance Imaging and Postmortem Computed Tomography in Ligature and Manual Strangulation

Abstract: The aim of this study was to evaluate magnetic resonance imaging (MRI) findings in cases of fatal manual or ligature strangulation. Verification of strangulation by computed tomography (CT), MRI, and at autopsy as well as its detectability in each modality was assessed. METHODS:We retrospectively analyzed 6 manual and ligature strangulation cases between 2013 and 2019 who all underwent a whole-body CT, head and neck MRI, and an autopsy. Two radiologists examined head and neck imaging data and compared the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This would be similar to the results of Hueck et al, who reported a Cohen’s Kappa coefficient of 0.54 for injuries of the laryngeal cartilages [ 9 ], albeit the group subsequently used different thresholds for the stated level of agreement. We also experienced the same difficulties in diagnosing laryngeal fractures as outlined by other groups, including decreased ossification [ 4 , 19 , 21 ], the size of the lesions [ 21 ] and non-displaced fractures [ 21 ]. However, there is considerable variation in the rate of detection of laryngeal fractures using PMCT within the medical literature.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This would be similar to the results of Hueck et al, who reported a Cohen’s Kappa coefficient of 0.54 for injuries of the laryngeal cartilages [ 9 ], albeit the group subsequently used different thresholds for the stated level of agreement. We also experienced the same difficulties in diagnosing laryngeal fractures as outlined by other groups, including decreased ossification [ 4 , 19 , 21 ], the size of the lesions [ 21 ] and non-displaced fractures [ 21 ]. However, there is considerable variation in the rate of detection of laryngeal fractures using PMCT within the medical literature.…”
Section: Discussionmentioning
confidence: 95%
“…It is well recognised that PMCT is superior to TIA in the identification of gas deposition within the body [ 9 ]. In hanging cases, fracture-associated gas bubbles and subcutaneous emphysema have been described, but again there is some variation in results/opinions across manuscripts [ 3 , 5 , 7 9 , 12 , 17 , 19 , 23 ]. Schulze et al reported that a ‘gas bubble sign’ was highly suggestive of laryngeal fractures in hanging cases with a positive-predictive-value of 95% and overall accuracy of 83%, but the study excluded decomposed decedents [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various internal injury findings can be identified in the context of a fatal strangulation as demonstrated by forensic autopsies and indicated by postmortem imaging procedures. These findings may include for example hemorrhages or edema in various soft tissue structures of the neck, lesions of the intimal layer of carotid arteries or fractures of the laryngeal skeleton or hyoid bone [1][2][3][4][5][6][7]. However, the vast majority of internal findings have in common that they are not visible in clinical forensic examinations of surviving victims of violence against the neck [3,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%